1993
DOI: 10.1103/physrevb.47.10201
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron-spectroscopy study of amorphousa-CNx:H

Abstract: We report in situ x-ray photoemission, ultraviolet photoemission (UPS), and electron-energy-loss photoelectron-spectroscopy studies of the electronic structure of nitrogen-containing amorphous hydrogenated carbon (a-CN:H). Films with different nitrogen concentrations are prepared by the ion-beamdeposition technique. The photoemission measurements do not reveal a shift in the Fermi level with respect to the top of the valence band, as would be expected from an n-type nitrogen-doping mechanism proceeding via sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(61 citation statements)
references
References 22 publications
7
54
0
Order By: Relevance
“…It indicates that the surface structure has become more graphitized with nitrogen incorporation into the surface. Mansour and Ugolini have also observed that nitrogen incorporation in amorphous hydrogenated carbon films favors graphitization [42]. From He I UPS valence band spectra, they noted increase in area and width of the p − π density of states (DOS) with increasing nitrogen content which is in accordance with the increase in size of the graphite like island due to clustering of π states in the aromatic rings.…”
Section: X-ray Photoelecron Spectroscopy (Xps) Studiessupporting
confidence: 53%
“…It indicates that the surface structure has become more graphitized with nitrogen incorporation into the surface. Mansour and Ugolini have also observed that nitrogen incorporation in amorphous hydrogenated carbon films favors graphitization [42]. From He I UPS valence band spectra, they noted increase in area and width of the p − π density of states (DOS) with increasing nitrogen content which is in accordance with the increase in size of the graphite like island due to clustering of π states in the aromatic rings.…”
Section: X-ray Photoelecron Spectroscopy (Xps) Studiessupporting
confidence: 53%
“…We would like to underline that our interpretation of the components of the N 1s and C 1s core level lines is coherent with the values of the binding energies ͑BE͒ of reference organic polymers containing nitrogen. Pyridine ͑CvN, sp 2 hybridization͒ has a C 1s BE at 285.5 eV 17,[25][26][27] and a N 1s BE at 400.6 eV. [25][26][27] Urotropine or HMTA ͑C-N, sp 3 hybridization͒, exhibits a C 1s BE at 286.9 eV ͓287.3 eV for hexamethylenetetramine ͑HMTA͔͒ 17,28-30 and a N 1s BE at 399.4 eV.…”
Section: A Core Level X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…Pyridine ͑CvN, sp 2 hybridization͒ has a C 1s BE at 285.5 eV 17,[25][26][27] and a N 1s BE at 400.6 eV. [25][26][27] Urotropine or HMTA ͑C-N, sp 3 hybridization͒, exhibits a C 1s BE at 286.9 eV ͓287.3 eV for hexamethylenetetramine ͑HMTA͔͒ 17,28-30 and a N 1s BE at 399.4 eV. The deconvoluted peaks from the C 1s spectra at Ϸ287 eV ͑C1͒ and from the N 1s spectra at Ϸ399 eV ͑N1͒ could also be assigned to CwN bonds 16,18,26,31 but the binding energy of the peak C1 in both the samples ͓Figs.…”
Section: A Core Level X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…Interestingly, they observed that nitrogen was able to increase the conductivity of a-C:H, and this has since been repeated by numerous other groups. [4][5][6][7][8][9][10] However, it has been unclear whether N increased the conductivity by doping-raising the Fermi level towards the conduction band, or by graphitization of the bonding-narrowing the band gap.…”
Section: Introductionmentioning
confidence: 99%